Effect of B4C on bending strength of ZTA ceramic reinforced high chromium cast iron matrix composites. Issue 8 (3rd August 2022) - Gao, Quan; Lu, Zhenlin; Jia, Lei; Wang, Yue
ABSTRACT: Zirconium dioxide-toughened aluminum oxide (ZTA) ceramic-reinforced high chromium cast iron (HCCI) matrix composites were prepared by vacuum pressure-free infiltration, and the effects of active additive boron carbide (B4 C) (10%, 12%) on the interface binding ability was studied systematically. Results showed the wettability between HCCI and ZTA could be improved after the addition of B4 C, which could result in a metallurgical combination by forming a transition layer. When the content of B4 C additive was 10%, the Brinell hardness of ZTA/HCCI composites reached 645 N/mm 2 in the as-infiltration state, and the bending strength was more than twice of HCCI. After heat treatment, the hardness and bending strength increased significantly, which reached 676.1 N/mm 2 and more than three times of HCCI, respectively. Graphical Abstract: uf0001